Traditional Chinese medicine additive capable of improving thunnus albacores meat quality - JI YUANYUAN (2017)
The invention relates to feed additives in aquaculture industry, in particular to a traditional Chinese medicine additive capable of improving thunnus albacores meat quality. The traditional Chinese medicine additive is prepared from the following raw materials in parts by weight: 30 to 60 parts of cortex magnoliae officinalis, 30 to 60 parts of pericarpium citri reticulatae viride, 10 to 30 parts of fructus quisqualis, 10 to 20 parts of white hyacinth bean, 25 to 45 parts of rhizoma smilacis glabrae, 15 to 35 parts of uncariae ramulus cum uncis, 20 to 40 parts of radix paeoniae alba, 50 to 90 parts of lotus leaf, 30 to 50 parts of kelp, 20 to 50 parts of jasmine flower, 30 to 60 parts of herba pogostemonis, 20 to 30 parts of caulis spatholobi, 10 to 20 parts of mushroom and 10 to 20 parts of lily bulb. The traditional Chinese medicine additive capable of improving thunnus albacores meat quality disclosed by the invention can enhance food intake of thunnus albacores, promotes thunnus albacores growth, saves a